Waste Management in Islamic Studies for Sustainable Environmental Preservation - Muhammad Faiz,; Agustiningsih , Maulida Dwi (Advances in Humanities and Contemporary Studies, 2023)
The world is experiencing an environmental crisis. Because of the lack of understanding of the community and government, the waste problem is neglected. Today most people know the adverse effects of garbage, including causing floods, diseases, and odors that can interfere with life, but the community's behavior does not balance this. Meanwhile, Islam teaches about cleanliness and environmental preservation. Environment and religion are often understood separately. The purpose of this study is to study waste management in Islamic studies for sustainable environmental preservation. The research was analyzed by a qualitative method. The data obtained are the theory and the results of previous studies. The 3R: Reduce, Reuse, and Recycle is a popular waste management model. Waste management is in line with Islam. In Islamic studies, the earth and its contents belong to Allah. Management and preservation have been written in the Qur'an. Humans should protect the environment, one of which is by implementing 3R in waste management. To achieve a sustainable environment, increasing waste management efficiency, restructuring policies to encourage efficiency in the recycling industry, and promoting environmentally friendly technologies are required.